SUCCESSFUL GLOBAL CLASSROOM INITIATIVE ENGAGES UHL2432 ENGLISH FOR PROFESSIONAL COMMUNICATION STUDENTS WITH INTERNATIONAL PARTNERS - Wan Noor Farah, Wan Shamsuddin; Hanisah, Kasbon (Centre for Modern Languages, 2024)
The Centre for Modern Languages at Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) recently celebrated the success of its Global Classroom initiative, a collaborative educational programme that connected UMPSA students with lecturers from The University of Auckland, Hiroshima University, Keio University, and industry partner ResMed.